The Contribution of Perceptions about the Tasks toward the Performance of School Counselor - Sry Rahmy Saputry; Herman Nirwana; Marjohan Marjohan (Jurnal Aplikasi IPTEK Indonesia, 2018)
The purposes of this study are to test the contribution of perceptions of school counselor about their task toward the performance of school counselor. This research used the quantitative approach with the descriptive-correlational method. The population was 303 school counselors and the sample consist of 169 people taken by Purposive Sampling technique. The instrument used was Performance of School Counselor Instrument with reliability score 0,861 and Perception about Tasks Instrument with reliability score 0,740. Data were analyzed using simple regression. The result of the research shows there is contribution (10,7%) of the perception of school counselor about their task toward the performance of school counselor in school